Fantasies of authenticity, anxieties of culture: global capital, entertainment and cultural nationalism in the contemporary popular cinemas of India and China since 1990 - de Feo-Giet, D (2016)
My thesis is dedicated to the study of popular, commercial cinema as a force within the discourse of national and personal identity in the rapidly changing mega-economies of India and China, and their diasporas, since the watershed year of 1990. Its purpose is to reveal the unique pattern of like and unlike that exists between the "Social Representations" (Serge Moscovici 2000) of contemporary India and China on screen through a juxtapositional comparative approach, close visual analysis, and the development of original theoretical tools. Tense networks of fantasy and anxiety emerge as popular culture actively circulates their shared experiences of changing global status, uneven economic growth (Gong Haomin 2012), and social change. Transnational subjects, Hua and Desi, arrive on screen ready to carve out culturally inflected modernities, in search of "tradition" and "values" to suit contemporary cultural-nations-beyond-borders. I treat film as consumer product, diegetic entity, and text: hence narrative, visual, linguistic and contextual aspects of over fourteen popular commercial films ("Bollywood" and "Yulepian" 娱乐片), are explored. My analysis comprises two interlocking halves: the first two chapters focus chiefly on identities - Hua and Desi, and diasporic persons. The former, conduits for the cultural nation to re-think modernity, the latter a dreamed vanguard of "claim-staking" ethnicised global consumers, defenders of the cultural nation in the "host" country. Chapters Three and Four focus on genres - comedy and history films. Through comedy, these films create state-serving heterotopias or challenge the status quo; perhaps they build cultural nationalist mythos, or lace cynical questions through lavish history film. To understand internecine relationships between economics, society and the imagination, entertainment film cannot be dismissed – in India and China, where change has had intended and unintended consequences unfolding even as uncertainty looms, I show that fresh study, especially in comparison, is absolutely essential.